2013
DOI: 10.1177/0218492312462224
|View full text |Cite
|
Sign up to set email alerts
|

External carotid-to-subclavian artery bypass in stent grafting of thoracic aorta

Abstract: Left external carotid-to-left subclavian artery bypass is a promising procedure in patients undergoing thoracic endovascular aortic repair that covers the orifice of the left subclavian artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…10) Also, Shimura et al reports the safety of external carotid to left subclavian artery bypass in patients who underwent thoracic endovascular aortic repair. 11) To the best of our knowledge, this is the first report for common carotid artery dissection secondary to surgical repair of Stanford type A AAD. The optimal intervention to achieve revascularization should be chosen on a case-by-case basis, and this surgical strategy could be an option.…”
Section: Discussionmentioning
confidence: 81%
“…10) Also, Shimura et al reports the safety of external carotid to left subclavian artery bypass in patients who underwent thoracic endovascular aortic repair. 11) To the best of our knowledge, this is the first report for common carotid artery dissection secondary to surgical repair of Stanford type A AAD. The optimal intervention to achieve revascularization should be chosen on a case-by-case basis, and this surgical strategy could be an option.…”
Section: Discussionmentioning
confidence: 81%
“…Compared to the number of carotid endarterectomies, subclavian artery reconstructions have been reported to constitute 4.6% (95% CE, 3.4%-6.1%) of surgeries [7]. Left external carotid-left subclavian artery bypass has been reported to be promising in patients with thoracic endovascular aortic repair occluding the mouth of the left subclavian artery [8]. Carotid-subclavian bypass performed in cases of subclavian steal syndrome due to atherosclerosis has been reported to show low mortality-morbidity and high long-term patency rates [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The most common anatomic variation of the supraaortic trunk is the aberrant right SA. Surgical indications for aberrant right SA are the aneurysm rupture risk, aneurysm compression symptoms, and embolic complications ( 4 ). There were no aneurysms and embolic complications in the aberrant right SA in our case.…”
Section: Discussionmentioning
confidence: 99%
“…But in general, the common carotid artery is preferred for inflow of the carotid-subclavian bypass. Shimura et al ( 4 ) performed a left ECA-left SA bypass in 15 patients who underwent TEVAR. The authors reported good patency of the graft during the follow-up period and had only one recurrent left laryngeal nerve palsy.…”
Section: Discussionmentioning
confidence: 99%